Importance of residents associations in guarded neighbourhoods: a review - Salleh, Nurulliza (CENTER OF REAL ESTATE STUDIES, 2016)
This review covers the important role of a residents’ association in governing a guarded neighbourhood. Nowadays, offering a guarded neighbourhood scheme has become a trend in the housing industry. There are two ways in establishing a guarded neighbourhood; that is through the developer or the residents. Problems arise in the establishement of a residents’ association due to the absence of legal provision that focuses on guarded neighbourhood management until it invites problems for the residents’ association to govern their neighboorhood. This practice raises the question whether there is a need for the residents’ association to govern their guarded neighbourhoods. Accordingly, using the residents’ association as a platform, this study will review some research conducted by other researchers regarding this issue. Thus, the findings show that the roles of the association are focused on managing safety, maintenance and care of common interest in the guarded neighborhood. Therefore, in order to strengthen the role of community associations, there is a need for better cooperation and communication between the residents ’ association with stakeholders such as residents and local authorities. It is concluded that the roles of residents' associations should be given more focus with more clarity.